Development of a Reflective Learning Program in Online Tutorials for the Biology Education Department - Mestika Sekarwinahyu; Amalia Sapriati; Ucu Rahayu (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to produce a reflective learning program that can be applied to the online tutorial in the Biology Education Department which can improve the reflective thinking skills of Biology Education students. The study was conducted in three years with using the research and development (R & D) which adapts the 4 D model from Thiagarajan et al. The research steps carried out preliminary studies, program design, program development -which includes program trials and program revisions-, and program implementation. What will be discussed in this paper is limited to how the program development process goes from the start until the right prototype is obtained to help students hone their reflective thinking skills. Reflective learning programs in online tutorials require several stages to arrive at the most appropriate prototype that is able to increase student participation in reflection which has the potential to increase reflective thinking skills. After going through several stages of testing and revising the placement of the most appropriate reflection activities, reflection activities are given every two sessions, namely in the second, fourth and sixth sessions